2015
DOI: 10.1002/glia.22953
|View full text |Cite
|
Sign up to set email alerts
|

Traumatically injured astrocytes release a proteomic signature modulated by STAT3‐dependent cell survival

Abstract: Molecular markers associated with CNS injury are of diagnostic interest. Mechanical trauma generates cellular deformation associated with membrane permeability with unknown molecular consequences. We used an in vitro model of stretch-injury and proteomic analyses to determine protein changes in murine astrocytes and their surrounding fluids. Abrupt pressure-pulse stretching resulted in the rapid release of 59 astrocytic proteins with profiles reflecting cell injury and cell death, i.e. mechanoporation and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 93 publications
(134 reference statements)
1
59
0
Order By: Relevance
“…FAO also ensures ATP production needed under different physiological or pathological conditions. In this regard, our observations that FAO enzymes are downregulated in spinal cord injury agree with a metabolic depression suggested after acute spinal cord trauma (Levine et al, ) and with observations that FAO is protective in stroke (Sayre et al, ). Thus we propose a role of FAO in brain disease progression and that its restoration could have a therapeutic benefit.…”
Section: Discussionsupporting
confidence: 91%
“…FAO also ensures ATP production needed under different physiological or pathological conditions. In this regard, our observations that FAO enzymes are downregulated in spinal cord injury agree with a metabolic depression suggested after acute spinal cord trauma (Levine et al, ) and with observations that FAO is protective in stroke (Sayre et al, ). Thus we propose a role of FAO in brain disease progression and that its restoration could have a therapeutic benefit.…”
Section: Discussionsupporting
confidence: 91%
“…These astrocyte extensions further couple the meningeal vasculature to axons [13, 14], and are involved in neural development and synapse formation [15], metabolic and ionic support of ONH axons [1618], facilitate mitochondrial transcellular degradation from retinal ganglion cell axons [19], and phagocytosis of myelin segments within the optic nerve [20, 21]. ONH astrocytes are also mechanosensitive [2224] and dynamically respond to elevated IOP by retracting or reorienting their extensions [8, 12]. The reaction of ONH astrocytes to elevated IOP may lead to loss of structural and biochemical support of axons and eventual axon degeneration [25–28].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the underlying mechanism, past studies have shown that STAT3-conditional knockout astrocytes expressed lower GFAP (31). We therefore hypothesized that STAT3 is potentially important in regulating the markers of A1 and A2.…”
Section: Discussionmentioning
confidence: 92%